A Member of the Delta Subgroup of Proteobacteria from a Pyogenic Liver Abscess Is a Typical Sulfate Reducer of the Genus Desulfovibrio - Schoenborn, Liesbeth (American Society for Microbiology, 2001)
Strain FH26001/95 (ATCC 700045) was previously isolated from a pyogenic liver abscess from a human. Comparative 16S rRNA gene sequence analysis showed that this strain is related to members of the delta subgroup of the proteobacteria, within a cluster of sulfate-reducing bacteria (Desulfovibrio spp.) and non-sulfate-reducing bacteria (Bilophila wadsworthia and Lawsonia spp.). The phenotype of strain FH26001/95 was found to be typical of members of the genus Desulfovibrio. Growth and substrate transformations were possible at oxygen concentrations of 2 to 5% (vol/vol) but not at oxygen concentrations of 21% (vol/vol) in air. Its isolation from an infection in a human suggests that some members of the genus Desulfovibrio can be considered opportunistic pathogens.